$${let}\:{f}\left({x}\right)\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:\:\frac{{dt}}{\mathrm{1}+{x}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }}\:\:{with}\:{x}>\mathrm{0} \\$$$$\left.\mathrm{1}\right){detemine}\:{a}\:{explicit}\:{form}\:{of}\:{f}\left({x}\right) \\$$$$\left.\mathrm{2}\right){find}\:{also}\:\:{g}\left({x}\right)\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:\:\frac{\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }}{\left(\mathrm{1}+{x}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }\right)^{\mathrm{2}} }{dt} \\$$$$\left.\mathrm{3}\right)\:{find}\:{the}\:{value}\:{of}\:{integrals}\:\:\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{{dt}}{\mathrm{1}+\mathrm{2}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }}\:{and}\: \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} \:\:\:\:\:\frac{{dt}}{\left(\mathrm{1}+\mathrm{2}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }\right)^{\mathrm{2}} } \\$$
$$\left.\mathrm{2}\right){we}\:{have}\:{f}^{'} \left({x}\right)\:=−\int_{\mathrm{0}} ^{\mathrm{1}} \:\:\frac{\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }{dt}}{\left(\mathrm{1}+{x}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }\right)^{\mathrm{2}} }\:=−{g}\left({x}\right)\:\Rightarrow{g}\left({x}\right)=−{f}^{'} \left({x}\right) \\$$$${rest}\:{to}\:{calculate}\:{f}^{'} \left({x}\right) \\$$$$\left.\mathrm{3}\right){changement}\:{t}\:={sht}\:{give}\:{I}=\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{{dt}}{\mathrm{1}+\mathrm{2}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }} \\$$$$=\int_{\mathrm{0}} ^{{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)} \:\:\:\frac{{ch}\left({t}\right){dt}}{\mathrm{1}+\mathrm{2}{ch}\left({t}\right)}\:=\int_{\mathrm{0}} ^{{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)} \:\:\frac{\frac{{e}^{{t}} \:+{e}^{−{t}} }{\mathrm{2}}}{\mathrm{1}+\mathrm{2}\frac{{e}^{{t}} \:+{e}^{−{t}} }{\mathrm{2}}}{dt} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)} \:\:\:\frac{{e}^{{t}} \:+{e}^{−{t}} }{\mathrm{1}+{e}^{{t}} \:+{e}^{−{t}} }{dt}\:\:=_{{e}^{{t}} ={x}} \:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\:\frac{{x}+{x}^{−\mathrm{1}} }{\mathrm{1}+{x}+{x}^{−\mathrm{1}} }\frac{{dx}}{{x}} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\:\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\:\frac{{x}^{\mathrm{2}} \:+\mathrm{1}}{{x}^{\mathrm{2}} \left(\mathrm{1}+{x}+{x}^{−\mathrm{1}} \right)}{dx}\:=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{x}^{\mathrm{2}} \:+\mathrm{1}}{{x}^{\mathrm{2}} \:+{x}^{\mathrm{3}} \:+{x}}{dx} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\:\frac{{x}^{\mathrm{2}} \:+\mathrm{1}}{{x}\left({x}^{\mathrm{2}} \:+{x}+\mathrm{1}\right)}{dx}\:\:{let}\:{decomposeF}\left({x}\right)=\frac{{x}^{\mathrm{2}} \:+\mathrm{1}}{{x}\left({x}^{\mathrm{2}} \:+{x}+\mathrm{1}\right)} \\$$$${F}\left({x}\right)\:=\frac{{a}}{{x}}\:+\frac{{bx}+{c}}{{x}^{\mathrm{2}} \:+{x}+\mathrm{1}} \\$$$${a}\:={lim}_{{x}\rightarrow\mathrm{0}} {xF}\left({x}\right)\:=\mathrm{1} \\$$$${lim}_{{x}\rightarrow+\infty} {xF}\left({x}\right)\:=\mathrm{1}\:={a}+{b}\:\Rightarrow{b}=\mathrm{1}−{a}=\mathrm{0}\:\Rightarrow{F}\left({x}\right)=\frac{\mathrm{1}}{{x}}\:+\frac{{c}}{{x}^{\mathrm{2}} \:+{x}+\mathrm{1}} \\$$$${F}\left(\mathrm{1}\right)\:=\frac{\mathrm{2}}{\mathrm{3}}\:=\mathrm{1}\:+\frac{{c}}{\mathrm{3}}\:\Rightarrow\mathrm{2}\:=\mathrm{3}\:+{c}\:\Rightarrow{c}\:=−\mathrm{1}\Rightarrow{F}\left({x}\right)=\frac{\mathrm{1}}{{x}}−\frac{\mathrm{1}}{{x}^{\mathrm{2}} \:+{x}+\mathrm{1}} \\$$$$\Rightarrow\:{I}\:=\frac{\mathrm{1}}{\mathrm{2}}\left\{\:\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \frac{{dx}}{{x}}−\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{dx}}{{x}^{\mathrm{2}} \:+{x}+\mathrm{1}}\right\} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)−\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{dx}}{{x}^{\mathrm{2}} \:+{x}+\mathrm{1}} \\$$$$\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{dx}}{{x}^{\mathrm{2}} \:+{x}+\mathrm{1}}\:=\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{dx}}{\left({x}+\frac{\mathrm{1}}{\mathrm{2}}\right)^{\mathrm{2}} \:+\frac{\mathrm{3}}{\mathrm{4}}}\:=_{{x}+\frac{\mathrm{1}}{\mathrm{2}}=\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}{u}} \:\frac{\mathrm{4}}{\mathrm{3}}\:\:\int_{\sqrt{\mathrm{3}}} ^{\frac{\mathrm{3}+\mathrm{2}\sqrt{\mathrm{2}}}{\mathrm{3}}} \:\frac{\mathrm{1}}{\mathrm{1}+{u}^{\mathrm{2}} }\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}{du} \\$$$$=\:\frac{\mathrm{2}}{\:\sqrt{\mathrm{3}}}\:\left[{arctanu}\right]_{\sqrt{\mathrm{3}}} ^{\frac{\mathrm{3}+\mathrm{2}\sqrt{\mathrm{2}}}{\mathrm{3}}} \:=\frac{\mathrm{2}}{\:\sqrt{\mathrm{3}}}\left\{\:{arctan}\left(\frac{\mathrm{3}+\mathrm{2}\sqrt{\mathrm{2}}}{\mathrm{3}}\right)−{arctan}\left(\sqrt{\mathrm{3}}\right)\right\}\Rightarrow \\$$$${I}\:=\frac{\mathrm{1}}{\mathrm{2}}{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)−\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}}\left\{{arctan}\left(\frac{\mathrm{3}+\mathrm{2}\sqrt{\mathrm{2}}}{\mathrm{3}}\right)−{arctan}\left(\sqrt{\mathrm{3}}\right)\right\} \\$$$$\\$$
$$\left.\mathrm{1}\right){f}\left({x}\right)\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:\:\frac{{dt}}{\mathrm{1}+{x}\sqrt{\mathrm{1}+{t}^{\mathrm{2}} }}\:\:{changement}\:{t}\:={sh}\left({u}\right)\:{give} \\$$$${f}\left({x}\right)=\int_{\mathrm{0}} ^{{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)} \:\:\frac{{chu}}{\mathrm{1}+{xchu}}{du}\:=\int_{\mathrm{0}} ^{{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)} \:\:\:\frac{\frac{{e}^{{u}} +{e}^{−{u}} }{\mathrm{2}}}{\mathrm{1}+{x}\frac{{e}^{{u}} +{e}^{−{u}} }{\mathrm{2}}}{du} \\$$$$=\:\int_{\mathrm{0}} ^{{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)} \:\:\:\:\frac{{e}^{{u}} +{e}^{−{u}} }{\mathrm{2}\:+{xe}^{{u}} \:+{x}\:{e}^{−{u}} }\:{du}\:\:=_{{e}^{{u}} ={z}} \:\:\:\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \frac{{z}+{z}^{−\mathrm{1}} }{\mathrm{2}+{xz}+{xz}^{−\mathrm{1}} }\frac{{dz}}{{z}} \\$$$$=\:\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\:\:\:\frac{{z}^{\mathrm{2}} \:+\mathrm{1}}{{z}^{\mathrm{2}} \left(\mathrm{2}+{xz}\:+{xz}^{−\mathrm{1}} \right)}{dz}\:=\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{z}^{\mathrm{2}} \:+\mathrm{1}}{\mathrm{2}{z}^{\mathrm{2}} \:+{xz}^{\mathrm{3}} \:+{xz}}{dz} \\$$$$=\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\frac{{z}^{\mathrm{2}} \:+\mathrm{1}}{{z}\left({xz}^{\mathrm{2}} \:+\mathrm{2}{z}+{x}\right)}{dz}\:{let}\:{decomposeF}\left({z}\right)\:=\frac{{z}^{\mathrm{2}} \:+\mathrm{1}}{{z}\left({xz}^{\mathrm{2}} \:+\mathrm{2}{z}+{x}\right)} \\$$$${xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}\:=\mathrm{0}\:\rightarrow\Delta^{'} \:=\mathrm{1}−{x}^{\mathrm{2}} \\$$$${case}\:\mathrm{1}\:\:\mathrm{1}−{x}^{\mathrm{2}} >\mathrm{0}\:\Rightarrow\mathrm{0}<{x}<\mathrm{1}\:\Rightarrow{z}_{\mathrm{1}} =\frac{−\mathrm{1}+\sqrt{\mathrm{1}−{x}^{\mathrm{2}} }}{{x}} \\$$$${z}_{\mathrm{2}} =\frac{−\mathrm{1}−\sqrt{\mathrm{1}−{x}^{\mathrm{2}} }}{{x}}\:\Rightarrow{F}\left({z}\right)\:=\frac{{z}^{\mathrm{2}} \:+\mathrm{1}}{{xz}\left({z}−{z}_{\mathrm{1}} \right)\left({z}−{z}_{\mathrm{2}} \right)} \\$$$$=\frac{{a}}{{z}}\:+\frac{{b}}{{z}−{z}_{\mathrm{1}} }\:+\frac{{c}}{{z}−{z}_{\mathrm{2}} } \\$$$${a}\:={lim}_{{z}\rightarrow\mathrm{0}} {zF}\left({z}\right)\:=\frac{\mathrm{1}}{{x}} \\$$$${b}\:={lim}_{{z}\rightarrow{z}_{\mathrm{1}} } \:\:\left({z}−{z}_{\mathrm{1}} \right){F}\left({z}\right)\:=\frac{{z}_{\mathrm{1}} ^{\mathrm{2}} \:+\mathrm{1}}{{xz}_{\mathrm{1}} \left({z}_{\mathrm{1}} −{z}_{\mathrm{2}} \right)}\: \\$$$${c}\:={lim}_{{z}\rightarrow{z}_{\mathrm{2}} } \:\:\left({z}−{z}_{\mathrm{2}} \right){F}\left({z}\right)\:=\frac{{z}_{\mathrm{2}} ^{\mathrm{2}} \:+\mathrm{1}}{{xz}_{\mathrm{2}} \left({z}_{\mathrm{2}} −{z}_{\mathrm{1}} \right)}\:\Rightarrow \\$$$${f}\left({x}\right)\:=\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} {F}\left({z}\right){dz}\:=\left[{aln}\mid{z}\mid+{bln}\mid{z}−{z}_{\mathrm{1}} \mid+{cln}\mid{z}−{z}_{\mathrm{2}} \mid\right]_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \\$$$$={aln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)+{bln}\mid\mathrm{1}+\sqrt{\mathrm{2}}−{z}_{\mathrm{1}} \mid+{cln}\mid\mathrm{1}+\sqrt{\mathrm{2}}−{z}_{\mathrm{2}} \mid−{bln}\mid\mathrm{1}−{z}_{\mathrm{1}} \mid \\$$$$−{cln}\mid\mathrm{1}−{z}_{\mathrm{2}} \mid \\$$$${case}\:\mathrm{2}\:\:\mathrm{1}−{x}^{\mathrm{2}} <\mathrm{0}\:\Rightarrow{x}>\mathrm{1}\:\:{f}\left({x}\right)=\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\frac{{z}^{\mathrm{2}} \:+\mathrm{1}}{{z}\left({xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}\right)}{dz} \\$$$${F}\left({z}\right)\:=\frac{{a}}{{z}}\:+\frac{{bz}\:+{c}}{{xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}} \\$$$${a}\:=\frac{\mathrm{1}}{{x}} \\$$$${lim}_{{z}\rightarrow+\infty} \:{zF}\left({z}\right)\:=\frac{\mathrm{1}}{{x}}\:={a}+\frac{{b}}{{x}}\:\Rightarrow\mathrm{1}\:={ax}\:+{b}\:\Rightarrow{b}=\mathrm{1}−{ax}=\mathrm{0}\:\Rightarrow \\$$$${F}\left({z}\right)\:=\frac{\mathrm{1}}{{xz}}\:+\frac{{c}}{{xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}} \\$$$${F}\left(\mathrm{1}\right)\:=\frac{\mathrm{2}}{\left(\mathrm{2}{x}+\mathrm{2}\right)}\:=\frac{\mathrm{1}}{{x}+\mathrm{1}}\:=\frac{\mathrm{1}}{{x}}\:+\frac{{c}}{\mathrm{2}{x}+\mathrm{2}}\:\Rightarrow\mathrm{1}\:=\frac{{x}+\mathrm{1}}{{x}}\:+\frac{{c}}{\mathrm{2}}\:\Rightarrow \\$$$$\frac{{c}}{\mathrm{2}}\:=−\frac{\mathrm{1}}{{x}}\:\Rightarrow{c}\:=\frac{−\mathrm{2}}{{x}}\:\Rightarrow\:{F}\left({z}\right)\:=\frac{\mathrm{1}}{{xz}}−\frac{\mathrm{2}}{{x}}\frac{\mathrm{1}}{\left({xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}\right)} \\$$$$=\frac{\mathrm{1}}{{x}}\left\{\:\frac{\mathrm{1}}{{z}}−\frac{\mathrm{2}}{{xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}}\right\}\:\Rightarrow{f}\left({x}\right)\:=\frac{\mathrm{1}}{{x}}\left\{\:\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\frac{{dz}}{{z}}−\mathrm{2}\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\frac{{dz}}{{xz}^{\mathrm{2}} \:+\mathrm{2}{z}+{x}}\right\} \\$$$$=\frac{\mathrm{1}}{{x}}{ln}\left(\mathrm{1}+\sqrt{\mathrm{2}}\right)−\frac{\mathrm{2}}{{x}}\:\int_{\mathrm{1}} ^{\mathrm{1}+\sqrt{\mathrm{2}}} \:\:\:\:\frac{{dz}}{{xz}^{\mathrm{2}} \:+\mathrm{2}{z}\:+{x}}\:=…. \\$$$$\\$$